2015
DOI: 10.1016/j.parkreldis.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and monitoring the symptoms of Parkinson's disease using smartphones: A pilot study

Abstract: Study sponsorshipThis study received no external funding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(270 citation statements)
references
References 10 publications
5
246
0
1
Order By: Relevance
“…voice, gait, falls) and physical activity can potentially be monitored continuously and in the patient's own daily environment. It is hoped that in the future, such information might be used by clinicians to make better-informed management decisions [122]. However, much work remains needed in this field, for example to demonstrate the feasibility of wearable sensor technology (e.g.…”
Section: Treatment Sitementioning
confidence: 99%
“…voice, gait, falls) and physical activity can potentially be monitored continuously and in the patient's own daily environment. It is hoped that in the future, such information might be used by clinicians to make better-informed management decisions [122]. However, much work remains needed in this field, for example to demonstrate the feasibility of wearable sensor technology (e.g.…”
Section: Treatment Sitementioning
confidence: 99%
“…Using wearable devices, various studies have shown that is possible to collect objective data regarding bradykinesia, tremor, dyskinesia, walking, sleep and speech that correlate to severity of disease, response to medication and track disease progression [87][88][89][90]. A recent study also showed that an intelligent closed-loop system integrating a wide range of wearable sensors, allowed physicians to remotely monitor the condition changes of the patients, adjust medication schedules, and individualize therapy in real-life conditions [91].…”
Section: Minimising Variability / Error In Assessing Endpointsmentioning
confidence: 99%
“…Discrete Fourier Transform converts samples of a function (a signal that varies over time) into the list of coefficients of a finite combination of complex sinusoids (ordered frequency that has sample value). Fast Fourier transform converts time (signal) to frequency by decomposing an N point time domain signal into N signals [4] and Detrended Fluctuation Analysis is a method to determine self-affection of a signal [5]. Often Spectral Analysis (SA) is used in signal processing for PD's motor symptom assessment.…”
Section: Sensors Signals and Measuresmentioning
confidence: 99%
“…Digitizing tablet is used almost for all types of symptoms. Smartphone [5] and Microsoft Kinect (motion detector, and depth sensor) [15] are the latest devices in the market used for this. Smartphones (new generation of sensing devices) could expand rapidly with PD motor symptom assessments.…”
Section: Sensors Signals and Measuresmentioning
confidence: 99%